COVERAGE OF DIRECTLY OBSERVED TREATMENT ACCORDING TO THE RISK OF TUBERCULOSIS/HIV COINFECTION AND UNFAVORABLE OUTCOMES - Laura Terenciani Campoy; Luiz Henrique Arroyo; Antônio Carlos Vieira Ramos; Rubia Laine de Paula Andrade; Marcos Augusto Moraes Arcoverde; Josilene Dália Alves; Ricardo Alexandre Arcêncio (Universidade Federal do Paraná, 2019)
Objective: To analyze the coverage of directly observed treatment according to the risk of tuberculosis/human immunodeficiency virus coinfection and unfavorable outcomes. Methods: Ecological study with secondary data related to 10,389 new cases of coinfection notified in the state of São Paulo, Brazil, from 2010 to 2015. They were analyzed by applying local Moran's index, spatial scan statistics, and hierarchical Bayesian models. Results: The São Paulo metropolitan area and Baixada Santista concentrate the highest incidence of coinfection and treatment default. Low coverage of directly observed treatment was associated with areas at risk for the coinfection and higher withdrawal risk. The city of São Paulo, the coastal region, and the Ribeirão Preto area showed a higher incidence of deaths, which did not show an association with the coverage of directly observed treatment. Conclusion: Low coverage of directly observed treatment was associated with a higher risk of coinfection and treatment default.